Teacher leadership practice : a case study of a public primary school in a semi-urban area of the Otjozondjupa Region, central Namibia - Hanghuwo, Maria Nahambo (Rhodes University, Faculty of Education, Department of Education, 2015)
The education system in Namibia was shaped by the policies located within the framework of the apartheid ideology. Since it gained its independence in 1990, the government positioned education at the top of the national priorities. Thus, there has been a growing realisation of the importance of more democratic forms of leadership in the education system for the country to be able to cater for a democratic society. Amongst others, teachers became active creators and managers of the learning outcomes. In addition, teachers are regarded as agents of change and the driving force for productive teaching and learning. Literature describes how the management in schools has been redistributing authority and power so that a culture of teacher leadership in school communities can grow. More importantly, school improvement depends more on the active involvement of teacher leaders as it is realised that people in formal positions cannot do everything. In this line this study investigated the understanding of teachers and members of management of teacher leadership practice and it further identified the structural and cultural factors which enabled and inhibited this practice in a primary school. This study is a case study of a Primary school in a semi-urban area of Otjozondjupa Region, a central part of Namibia. This study was conducted in the interpretive paradigm and it is a qualitative case in nature, employing semi-structured interviews, observation and document analysis. Triangulation over the data revealed that respondents have an understanding of the concept and that all teachers are involved in leadership roles at school which are more strongly found in the classroom and through involvement with other teachers. Teacher leadership roles at the case study school also occur within the whole school with some limitations and also extend beyond the school. Grant's (2008) model of teacher leadership was used to analyse the data. The study suggested some hindrances and supporting factors of teacher leadership. The findings suggested that teacher leadership is understood at the case study school and that they experienced factors that enabled and hindered this practice at different stages. Enabling factors included the school structure, further studies and workshops attended, while teacher leadership is impeded by teachers' unwillingness to collaborate with others and the platoon system. The study recommends future large scale studies, including at secondary schools, so that a broader sense of teacher leadership may emerge.
Keywords: Democracy and education -- Study and teaching (Elementary) -- Namibia; Educational leadership; Teacher participation in administration